Kinetics of Rituximab Excretion into Urine and Peritoneal Fluid in Two Patients with Nephrotic Syndrome. (24th January 2017) - Stahl, Klaus; Duong, Michelle; Schwarz, Anke; Wagner, A. D.; Haller, Hermann; Schiffer, Mario; Jacobs, Roland
Abstract : Clinical observations suggest that treatment of Rituximab might be less effective in patients with nephrotic range proteinuria when compared to nonnephrotic patients. It is conceivable that the reason for this is that significant amounts of Rituximab might be lost in the urine in a nephrotic patient and that these patients require a repeated or higher dosage. However, this has not been systematically studied. In this case report we describe two different patients with nephrotic range proteinuria receiving Rituximab. The first patient received Rituximab for therapy resistant cryoglobulinemic membranoproliferative glomerulonephritis and the other for second line treatment of Felty's syndrome. We employed flow cytometry to determine the amount of Rituximab excretion in both urine and peritoneal fluid specimens in these patients following administration of Rituximab. We found that a significant amount of Rituximab is lost from the circulation by excretion into the urine. Furthermore we saw a close correlation of the excretion of Rituximab to the excretion of IgG molecules suggesting selectivity of proteinuria as the determining factor of Rituximab excretion. Further larger scale clinical studies could have the potential to evaluate an optimal cut-off value of IgG urinary loss before a possible administration of Rituximab therefore contributing to a more individualized treatment approach in patients with nonselective and nephrotic range proteinuria.